THE STUDY OF DISPLACEMENT OF THE ABOMASUM IN THE REGION OF TETOVO – MACEDONIA - Dashamir Mamuti; Erinda Lika; Paskal Gjino; Musa Doko (European Scientific Journal, ESJ, 2012)
The displacement of abomasum in cows is a relatively new pathology that follows step by step throughout the intensification of their growth. Abomasum incidence of displacement in cows ranges from 10-15% of the number of heads that increase to milk production throughout the last 10-year-old and mainly affects heads with high efficiency in milk production [2, 5, 20]. The displacement of the abomasum is the most serious pathology in cows which often have lethal outcome. The Abomasal disorders within topographic shift can mostly be observed in cows with high yield, in the first period after calving and early lactation. By this pathology get affected best herds of cows for milk production. The incidence of displacement of abomasal disorder is different. It depends on the breed, production level and nature of feeding by displacement of abomasum get affected by the shift from 4 - 12 % of cows. This pathology is diagnosed in recent years in the region of Tetovo in herds of cows for milk production realised in high production level from 7000 up to 10 000 litres per head in lactation. In the clinical practice, there is already a good experience in the diagnosis of this pathology. For the year 2010 – 2011 in the Tetovo region farms the presence of the abomasal displacement was observed in 12 heads or 2.4 % of heads in lactation. In heads (83.3%) was the displacement on the left and in 2 cases (16.6 %) abomasum displacement was on the right side. After treatments of cows with displacement abomasal were cured clinically only 2 heads (16.6 %) while 7 heads (58.3%) completed the premature slaughter and 3 heads (25%) died.